Comparison of FT-NIR and NIR for evaluation of phyisco-chemical properties of stored wheat grains. Issue 3 (3rd July 2018) - Pandey, Pooja; Srivastava, Shubhangi; Mishra, Hari Niwas
Abstract: Objectives: Storage studies were carried out in wheat grains with different moisture contents, level of infestation, and storage days. Material and Methods: Wheat grain samples were infested with Rhyzopertha dominica and stored for up to 90 days under ambient conditions. Every 45 days, samples of wheat were collected and evaluated for protein, fat, ash, 1000 kernel weight, and hardness. Results: The physicochemical parameters, namely, protein, 1000 kernel weight, and hardness decreased while fat and ash content increased with the storage. Methodology for identification of infested samples was developed in Fourier transform near infrared (FT-NIR) and near infrared (NIR) using infested wheat and control samples. The linear regression plots for different quality parameters gave an R 2 value of 82.04% and 97.15% via FT-NIR and 81.61% and 98.07% via NIR. The RMSEP values by NIR were in the range of 0.03 to 0.7, whereas the RMSECV values of FT-NIR were in the range of 0.03 to 1.2. Conclusions: Both the models performed well for the cross validation studies; hence, they can be used in future for the rapid assessment of storage quality of wheat grains.